High resolution photoionisation spectroscopy of vibrationally excited Ar center dot NO - Monti, O; Cruse, H; Softley, T; Mackenzie, S (2001)
Mass-analysed threshold ionisation (MATI) spectra of the Ar·NO complex have been obtained for the first time. These spectra have been used to determine unambiguously the nature of three bands detected by resonance-enhanced multiphoton ionisation (REMPI) spectroscopy via the Ã state of Ar·NO. The features are shown to originate from vibrationally excited states of Ar·NO in its electronic ground state. The assignment is in agreement with recent theoretical calculations. © 2001 Elsevier Science B.V.